Cross-disciplinary approaches towards smart, resilient and sustainable circular economy. (20th September 2019) - Fan, Yee Van; Lee, Chew Tin; Lim, Jeng Shiun; Klemeš, Jiří Jaromír; Le, Phung Thi Kim
Abstract: Environmental sustainability has gained increasing attention in recent years due to the evident impacts of rapid economic growth and urbanisation. Efficient resources and utility management is one of the vital strategies to minimise waste/losses, pollution and extraction of virgin resources. It facilitates the development of a circular economy. This review discusses the cross-disciplinary approaches devoted to clean technologies, process modelling, monitoring and management framework in the effort to mitigating GHG, air (causing, e.g. smog/haze) and water pollution. The review focuses on the roles of (a) Energy and water management, (b) Waste management and (c) Green policy and pollution minimisation strategies. Each section is divided into two sub-sections starting with the introduction on the assessed areas, followed by the sections based on the latest contribution of a Special Volume and the proposed direction for future research. This review suggests (i) More studies based on case studies in real life context and prototypes involving consensus building among the stakeholders, proven by viable economic feasibility analyses, are needed to enable environmental sustainability. (ii) Data availability, enabling policy and cost of investment is the common barrier to put the proposed solutions or methodologies into practice. (iii) Substantial improvement of environmental sustainability can be benefited through the waste (solid, water, heat) recovery. Highlights: Connecting the circular economy to three areas of resources and utilities management. Assesses the development of energy, water and waste management for environmental sustainability. Assesses the existing green policy and strategies. Identifies the emerging measures and the potential research directions.